Analisis Hpp Bakso Udang Dengan Metode Full Costing (Kasus UD. Tani Bina Sejahtera Kab. Gresik) - Klaudensia Hermalia; Humaidi, Faisol (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
As a small business that tends to have limited information and weak understanding in developing its business, small and medium enterprises (MSMEs) such as UD Tani Bina Sejahtera actually need input through research materials that can be used as a guide in developing their business. In research conducted at UD Tani Bina Sejahtera, it turned out that the method for calculating HPP for its business activities was still not detailed. The full costing method is the method used by researchers in this research. This is a method for determining the cost of production which takes into account all elements of production costs in the cost of production, which consists of raw material costs, direct labor costs and factory overhead costs, both fixed and variables. The data analysis technique used is descriptive quantitative analysis, namely analysis by detailing and explaining at length the relationship between research data in sentence form. The research results showed that the calculation of the cost of production using the full costing method compared with the cost of production used by the company's calculations gave different results. The cost of production calculated using the full costing method produces a slightly higher figure. This is because the full costing method uses the BOP rates charged, while according to the company the calculation of factory overhead costs uses the actual BOP. Keywords: HPP, full costing, BOP